Pendampingan kajian kitab ramadhan dengan integrasi pendekatan klasik dan digital di Pondok Pesantren Bustanul Ulum Krai Lumajang dan Fatihul Ulum Klatakan Tanggul Jember - Munawwaroh, Munawwaroh; Hasanah, Uswatun; Iflaha, Nurul; Arifin, Zainur (Lembaga Penerbitan, Penelitian, dan Pengabdian Masyarakat (LP3M) UNZAHLP3M, 2025)
The tradition of kitab kuning studies in pesantren faces effectiveness challenges in the digital era, primarily due to the limited use of technology and low digital literacy among students and instructors. This community service initiative aims to optimize kitab kuning learning management, enhance instructor capacity, facilitate digital access, and build a structured evaluation system. Using a participatory action research method, this activity focuses on training, mentoring, utilizing digital kitab applications, and online evaluation. Data was collected through observation, interviews, activity documentation, and Google Forms. The subjects of this initiative were students and ustadz from Pondok Pesantren Bustanul Ulum Krai Lumajang and Fatihul Ulum Klatakan Tanggul Jember. These individuals were familiar with digital devices but had not yet optimally used them for kitab learning activities. The program successfully optimized the classic approach to kitab kuning learning while integrating digital technology. Furthermore, there was an increase in the capacity of lecturers and instructors, as well as mentorship for students. As a result, students showed holistic development (cognitive, affective, psychomotor), and a transformation in learning management occurred within the partner pesantren. This transformation followed Lewin's three stages of change: unfreezing (opening up to technology), changing (implementing an integrative learning system), and refreezing (standardizing new adaptive and value-based patterns). This initiative also produced various digital literacy products and workshops, serving as platforms for reflection, evaluation, reinforcing pesantren values, and strengthening value-based innovation management.